Active Citizen Participation in E-Government 2012
DOI: 10.4018/978-1-4666-0116-1.ch027
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of Trust in the e-Government Context

Abstract: Although trust aspects have been investigated in e-commerce context, the e-government field is still significantly lacking from empirical studies that explore trust in e-government from the citizen’s perspective. The lack of trust in e-government in developing countries is another persuasive impetus for conducting this study. The few recent studies investigating citizens’ trust in e-government are conducted in developed countries. This study employed a qualitative approach (focus groups) to gain in depth under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…To discuss the influence of trust in context of egovernment services, it was observed that previous literature has identified trust as the most significant factor towards citizen's intention to use egovernment services (Abu-Shanab, 2014; Alsaghier and Hussain, 2012;Ranaweera, 2016;Rehman et al, 2016;Roy et al, 2015). Trust has been mentioned as an essential requirement for the successful implementation of e-government services.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…To discuss the influence of trust in context of egovernment services, it was observed that previous literature has identified trust as the most significant factor towards citizen's intention to use egovernment services (Abu-Shanab, 2014; Alsaghier and Hussain, 2012;Ranaweera, 2016;Rehman et al, 2016;Roy et al, 2015). Trust has been mentioned as an essential requirement for the successful implementation of e-government services.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…This includes broken links, multiple channels for information/service access, especially mobile devices, and personalisation of the e-services. Alsaghier and Hussain (2012) showed that broken links in e-government websites resulted in a lack of trust by users regarding the website. Dolan (2015) even suggested that a fully functional e-government website is one that has no broken links.…”
Section: Quality Of Information and Servicesmentioning
confidence: 99%
“…This indicates that anytime a user clicks on a link to the website, there is more than a 0.5 probability that the user will be taken to an inaccessible page/content. This is worrisome, given that broken links frustrate users and reduce their chances of revisiting, as well as increasing the user's lack of trust in the e-government website as emphasised by Alsaghier and Hussain (2012). It has been postulated that citizen trust in government will increase when they have 24/7 access to government information (Karkin & Janssen, 2014).…”
Section: Broken Linksmentioning
confidence: 99%
See 2 more Smart Citations